2008
DOI: 10.1507/endocrj.k08e-075
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinological Analysis of 122 Japanese Childhood Cancer Survivors in a Single Hospital

Abstract: Abstract. With recent improvements in the diagnosis and treatment of cancer, the number of childhood cancer survivors (CCSs) has been increasing in Japan. The importance of quality of life during the lifetime of CCSs has now been recognized, and the late effects of cancer treatments are essential and important issues. In this study we analyzed the endocrinological abnormalities of CCSs by retrospectively evaluating 122 outpatients (62 males and 60 females) who had been referred from pediatric oncologists to ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 28 publications
(33 reference statements)
4
47
0
Order By: Relevance
“…The cure rates and the quality of cure are very important parameters for CCS. The results of the present study significantly contribute to the published literature because very few studies have comprehensively surveyed the late effects and QOL of CCS after treatment with SCT in Japan [17,18,20].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The cure rates and the quality of cure are very important parameters for CCS. The results of the present study significantly contribute to the published literature because very few studies have comprehensively surveyed the late effects and QOL of CCS after treatment with SCT in Japan [17,18,20].…”
Section: Discussionmentioning
confidence: 73%
“…The health status and extent of organ damage might affect the health-related quality of life (QOL) of long-term childhood cancer survivors (CCS) [9,10]. Many comprehensive reviews have been published in western countries (USA and Europe) on the late effects in CCS treated with SCT [11][12][13][14][15][16]; however, information on CCS treated with SCT in Asian countries including Japan is hitherto limited [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Infertility or impaired reproductive outcome is also an important problem for CCSs [8,9]. Our group has reported endocrinological abnormalities in 67% and gonadal dysfunction in 49% of 122 CCSs [10]. Chemotherapy, radiation therapy, and conditioning for hematopoietic stem cell transplantation (HSCT) can damage gonadal germ cells and alter the production of gonadal hormones [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we found normal BMI and normal percentage fat in NHL survivors. Hypothyroidism, which can contribute to obesity and is reported in survivors, especially after local radiotherapy [49][50][51], did not occur in this group of survivors.…”
Section: Discussionmentioning
confidence: 49%